A global perspective of entrepreneurship and innovation in China. Issue 4 (29th October 2018) - Ahlstrom, David; Yang, Xiaohua; Wang, Liang; Wu, Changqi
Abstract : Purpose: This paper aims to study largely recent aspects of entrepreneurship and innovation in China. It synthesizes the research in the current special issue (SI) of Multinational Business Review (MBR) on this topic. In addition, this paper differs from other work on this topic in examining entrepreneurship and innovation from a more global standpoint with relevant international effects. Design/methodology/approach: The paper provides an overview of the literature on entrepreneurship, innovation and key related topics such as firm and economic growth, as well as linking this research to related international works. It also summarizes the papers of the SI. Findings: The authors' analysis suggests that the study of entrepreneurship and innovation should be placed in the context of a country's economic development and institutional environment as well as the firm internationalization trajectories and business models. In addition, the authors believe that a good understanding of economic growth in a transition economy like China (which is a key goal of China's recent emphasis on innovation) is facilitated by understanding the comparative advantages and disadvantages of an economy with respect to the global innovation system. Originality/value: The authors' study explores the local-global and parent-subsidiary connectivity and co-evolution of firm strategies and the institutional environment in entrepreneurship and innovation in emerging and transition economies. The authors summarize and synthesize the papers in this SI to provide the results as well as some directions for future research in the domain of entrepreneurship, innovation and new venture creation, which is believed to be a key engine of economic growth in the coming years.